2023
DOI: 10.1002/nml.21563
|View full text |Cite
|
Sign up to set email alerts
|

How can nonprofit boards innovate for growth? An integrative‐systematic review

Abstract: Despite the nonprofit sector's significance in economic contribution, workforce, and social impact, it faces unique innovation hurdles and is not well positioned for sustainability, growth, and prosperity. However, with only a partial, disconnected view from the extant research, we do not understand the relationship between boards and nonprofit innovation for growth. To address this problem, we conducted a systematic literature review drawing on 27 studies published since 2000 to provide a first‐in‐field and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 103 publications
(162 reference statements)
0
3
0
Order By: Relevance
“…This contrasts with some prior research that found a positive relationship between gender diversity and innovation (Galia & Zenou, 2013;Miller & Del Carmen Triana, 2009). However, as highlighted in the literature, board composition and diversity alone are insufficient to drive innovation-organizational practices and processes play a key enabling role (Holgersson & Hvenmark, 2023;Richardson et al, 2023). Even when female representation on boards increases, unequal participation and out-group biases can persist, limiting cognitive diversity benefits (Jaskyte, 2012;Torchia et al, 2018).…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…This contrasts with some prior research that found a positive relationship between gender diversity and innovation (Galia & Zenou, 2013;Miller & Del Carmen Triana, 2009). However, as highlighted in the literature, board composition and diversity alone are insufficient to drive innovation-organizational practices and processes play a key enabling role (Holgersson & Hvenmark, 2023;Richardson et al, 2023). Even when female representation on boards increases, unequal participation and out-group biases can persist, limiting cognitive diversity benefits (Jaskyte, 2012;Torchia et al, 2018).…”
Section: Discussionmentioning
confidence: 73%
“…Boards contribute to an organization's performance and innovation by providing advice and unique leadership contributions (Castanias & Helfat, 1991Zahra et al, 2000). The composition of board is considered as one of the key factors related to innovation in nonprofits (Richardson et al, 2023). Board members' diverse professional knowledge, skills, and experiences can also contribute to strategic decision-making and organizational innovation.…”
Section: The Role Of Board Diversity In Innovationmentioning
confidence: 99%
See 1 more Smart Citation